Beyond Belief: Sovereignty and the Spectacle of Martyrdom in Early Modern France. (December 2014) - Blanchard, Jean-Vincent
<x content-type="archive" xml:space="preserve">Abstract</x> Corneille's theater exemplifies how violence founded the State of Louis XIII and Cardinal Richelieu as an embodied, affective, and lived reality. Through the lens of vivid Catholic representations of martyrdom, such as those 'spiritual exercises' proposed by the Jesuit Louis Richeome in La Peinture spirituelle (1611), and in the highly prescriptive context of classical dramaturgy and theatrical aesthetics of seventeenth-century France, this article shows how Corneille's Polyeucte (1641) produced performative effects that corporealised those subjects of the French monarch's sovereign power, locating them in a historicized understanding of religious revelation and salvation.